Circadian and developmental regulation of N-methyl-d-aspartate-receptor 1 mRNA splice variants and N-methyl-d-aspartate-receptor 3 subunit expression within the rat suprachiasmatic nucleus - Bendová, Z; Sumová, A; Mikkelsen, J D (Neuroscience, 2009)
The circadian rhythms of mammals are generated by the circadian clock located in the suprachiasmatic nucleus (SCN) of the hypothalamus. Its intrinsic period is entrained to a 24 h cycle by external cues, mainly by light. Light impinging on the SCN at night causes either advancing or delaying phase shifts of the circadian clock. N-methyl-d-aspartate receptors (NMDAR) are the main glutamate receptors mediating the effect of light on the molecular clockwork in the SCN. They are composed of multiple subunits, each with specific characteristics whose mutual interactions strongly determine properties of the receptor. In the brain, the distribution of NMDAR subunits depends on the region and developmental stage. Here, we report the circadian expression of the NMDAR1 subunit in the adult rat SCN and depict its splice variants that may constitute the functional receptor channel in the SCN. During ontogenesis, expression of two of the NMDAR1 subunit splice variants, as well as the NMDAR3A and 3B subunits, exhibits developmental loss around the time of eye opening. Moreover, we demonstrate the spatial and developmental characteristics of the expression of the truncated splice form of NMDAR1 subunit NR1-E in the brain. Our data suggest that specific properties of the NMDAR subunits we describe within the SCN likely influence the photic transduction pathways mediating the clock entrainment. Furthermore, the developmental changes in NMDAR composition may contribute to the gradual postnatal maturation of the entrainment pathways.
Keywords: cirkadiánní rytmus; messenger RNA; Female; analýza rozptylu; novorozená zvířata; Analysis of Variance; Receptors, N-Methyl-D-Aspartate; krysa rodu Rattus; zvířata; potkani Wistar; receptory N-methyl-D-aspartátu; protein - isoformy; Circadian Rhythm; Animals, Newborn; Gene Expression Regulation, Developmental; Protein Isoforms; RNA, Messenger; ženské pohlaví; nucleus suprachiasmaticus; Rats, Wistar; Male; embryo savčí; Rats; vývojová regulace genové exprese; Animals; mužské pohlaví; Suprachiasmatic Nucleus; Embryo, Mammalian